Quantitative evaluation of anti-biofilm cavitation activity seeded from microbubbles or protein cavitation nuclei by passive acoustic mapping - Keller, SB; LuTheryn, G; Gray, MD; Lyons, B; Cleveland, RO; Stride, E; Coussios, CC (IOP Publishing, 2024)
Objective Bacterial biofilms represent a major challenge for effective antibiotic therapy as they confer physical and functional changes that protect bacteria from their surrounding environment. In this work, focused ultrasound in combination with cavitation nuclei was used to disrupt biofilms of S. aureus and P. aeruginosa, both of which are on the World Health Organization's priority list for new antimicrobial research.